2020
DOI: 10.1186/s40814-020-00589-y
|View full text |Cite
|
Sign up to set email alerts
|

A protocol for a pilot cluster randomized control trial of e-vouchers and mobile phone application to enhance access to maternal health services in Cameroon

Abstract: Background: Cameroon still has relatively high maternal mortality rate (MMR) of 596/100,000 live births. Approximately 40% of births are unattended by skilled healthcare personnel with high out-of-pocket expenditures. Poor resource allocation, poorly functioning referral systems, long trekking distances to health facilities, all of which lead to low rates of use of maternal health services. Objectives: The aim of this pilot study is to explore perception and acceptability of mobile health (mhealth) and e-vouch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Two programs in Uganda adopted the mobile phone system midway through the implementation [ 35 , 116 ], whereas three programs in Kenya were initially designed for using mobile money or a mobile e-voucher platform [ 75 , 76 , 78 ]. One study from Cameroon was discussed as a pilot protocol for the mobile e-voucher [ 29 ] and another program in Tanzania provided mobile phone credit vouchers for direct two-way communication between pregnant women and healthcare providers [ 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two programs in Uganda adopted the mobile phone system midway through the implementation [ 35 , 116 ], whereas three programs in Kenya were initially designed for using mobile money or a mobile e-voucher platform [ 75 , 76 , 78 ]. One study from Cameroon was discussed as a pilot protocol for the mobile e-voucher [ 29 ] and another program in Tanzania provided mobile phone credit vouchers for direct two-way communication between pregnant women and healthcare providers [ 79 , 80 ].…”
Section: Resultsmentioning
confidence: 99%
“…For cross-validation purposes, the logic model developed from this interpretive synthesis of evidence was compared with a logic model published in a previous study on the mobile maternal health e-voucher program in Cameroon [ 29 ]. All the elements identified from their study were already included in the logic model developed from this systematic review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These mHealth interventions reduce the myriads of constraints such as distance, time, access that are typical of RMNCH service delivery in sub-Saharan Africa ( 8 , 9 ). While studies have shown the effectiveness of mHealth in delivering RMNCH services ( 4 , 7 – 9 ), there is little information about stakeholder's involvement in the design and implementation of mhealth interventions including factors that enhance mHealth services utilization in low-cost settings, as access to mobile phones does not guarantee RMNCH service utilization ( 1 , 10 ).…”
Section: Introductionmentioning
confidence: 99%